Forensic Assistance Project: Consultant Report 1999-031 Kalinovik I Federation Commission on Missing Persons - Bosniak Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: York, Heather On 24 and 25 June 1999 the Federation Commission on Missing Persons - Bosniak Side recovered the remains of 14 individuals from two of three investigated sites near Kalinovik. Place of Exhumation: Kalinovik Exhumation Site: Kalinovik I, Kalinovik II, Borovac Date of Exhumation: 24-25 June 1999 Minimum Number of Exhumed Individuals: 014